Green intellectual capital and financial performance: The moderate of family ownership - Anna Sutrisna Sukirman; Wiwiek Dianawati (Cogent Business & Management, 2023)
This study aims to determine the effect of green intellectual capital disclosure on the company's financial performance, which is then moderated by family ownership. The concept of green intellectual capital disclosure consists of three dimensions: green human capital, green structural capital, and green relational capital. While the company's financial performance is obtained from the company's return on equity. The study uses secondary data for companies listed on the Indonesia Stock Exchange for three financial reporting periods starting from 2019 to 2021 in mining sector companies and basic and chemical industry sector companies, totaling 92 companies. The reason for choosing these companies is because these two sectors have a fairly high level of influence and sensitivity to the environment. The findings of this study's statistical analysis demonstrate that disclosure of a company's green intellectual capital has no direct impact on its financial success. The relationship between company financial success and disclosure of green intellectual capital can be strengthened by family ownership, which acts as a moderating variable. This study has limitations that can be an opportunity for future research, namely not testing all company sectors (except the banking sector) listed on the Indonesia Stock Exchange, so that green intellectual capital disclosure is still limited to companies that have a level of influence or sensitivity to the environment. More testing still needs to be done by increasing the number of company samples and research observation years. This research has practical implications, namely for the government to pay more attention to the environmental interests of the company's operational activities so that the company's financial performance is better but does not damage the environment, and for many investors who care about the environment (commonly known as the green concept"). This study has limitations, namely only testing two company sectors; it is hoped that future research will test more company sectors except the banking sector. This research has never been conducted in previous studies that develop concepts, test the relationship between green intellectual capital disclosure and financial performance directly, and make family ownership a moderator.
Keywords: 650; family ownership; financial performance; Green intellectual capital disclosure